Deli dan Sumatera Timur dalam Pusaran Politik Kawasan Kolonial Belanda - Syaiful Anwar (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This paper discusses the regional politics that occurred in the land of Deli and the Residency of East Sumatra during the Dutch colonial period. The formation of administrative areas is influenced by various conditions such as topography, culture, economy, and politics. The focus of the study in this paper lies in the political influence that shaped Deli and East Sumatra as part of the colonial administration in the Dutch East Indies region. The qualitative method is the tendency to discuss this historical study involving heuristics through various kinds of literature, criticisms, interpretations, and historiography. The study results show that the area known as North Sumatra today has started from the establishment of Deli as a sovereign territory, the emergence of various sultanates around it, to clustering in the administrative map of East Sumatra as part of the Dutch East Indies region.